5PSQ-006 Impact of PUIzzle, a playful educational tool on high-alert medications on healthcare professionals' knowledge: a 7-months analysis. Issue 1 (23rd March 2023) - Chen, E; Lamand, V; Catala, L; Caré, W; Nielly, H; Broncard, C; Reynaud, B; Antoine, AL
Abstract : Background and Importance: High-alert medications (HAMs) can lead to serious adverse events when errors occur during the drug management. To raise awareness among healthcare professionals (HCPs), our hospital pharmacy has developed a fun educational tool in puzzle form: PUIzzle (PUI is the French acronym for internal use pharmacy). Aim and Objectives: To evaluate PUIzzle's impact on HCPs' knowledge on HAMs, as well as participants' satisfaction. Material and Methods: Our monocentric study took place in a 300-bed hospital in Paris region (France) between January and August 2022. No ethical approval for the study was requested as participation was voluntary and anonymous. PUIzzle consists of 12 pieces containing general information on HAMs and a description of their management, monitoring and antidotes. A question-card is associated with each puzzle piece. To assess their knowledge, participants completed a pre- and post-training questionnaire consisting of five multiple-choice questions, with a total score ranging from 0 to 5. They also completed a satisfaction questionnaire consisting of four items rated from 1 'dissatisfied' to 4 'very satisfied'. Results: A total of 147 participants were trained during 39 sessions: 92 nurses, 17 pharmacy technicians, 17 paramedical students, 12 caregivers, 7 healthcare students, 1 pharmacist and 1 physician. Session median duration was 60 minutes [min=55 ; max=110]. The average knowledge scores before and after training (AFT) were respectively 1.1/5 and 3.1/5 (+40%). Before training, 54 (37%) HCPs had a score of 0, versus 4 (3%) AFT, 43 (29%) a score of 1, versus 20 (14%) AFT, 34 (23%) a score of 2, versus 21 (14%) AFT, 13 (9%) a score of 3 versus 42 (29%) AFT, 3 (2%) a score of 4, versus 35 (24%) AFT. Twenty-five HCPs (17%) achieved the highest score of 5, only AFT. A significant improvement (p<0.001) with an average increase of +2 points (σ=0.104) was observed. Regarding satisfaction of the training, participants attributed an average score of 3.8/4 (σ=0.096). Conclusion and Relevance: PUIzzle is a fun educational tool that significantly improves HCP's knowledge on HAMs. Suitable to all HCPs, this training will gradually be extended to more physicians. Therefore, PUIzzle will be part of a continuing education programme on drug-induced adverse events implemented at our institution. References and/or Acknowledgements: Conflict of Interest: No conflict of interest